FUZZY TOPSIS BASED SOLAR PV DESIGN OPTIMIZATION - Dunkcurn Niem A, Dakeh (Universiti Malaysia Sarawak (UNIMAS), 2023)
Due to the Sarawak Corridor of Renewable Energy (SCORE) development plan with collaboration of Sarawak Energy Berhad, Sarawak pledged to begin the implementation of clean energy resources. Other than abundant resources of hydro, solar energy is one of the preferred renewable energy as the sun is an endless clean energy source. Thus, solar PV design has been researched and studied broadly decades before with solar technologies seeing stable improvements in efficiency and reliability over the years to cope with the demand. Solar PV design is dependent on several parameters which includes the capacity of power needed, availability of solar energy within the area all year, power losses within the system, and sizing of the required components. Inevitable technological shortcoming and the appropriate configuration and sizing of a solar PV system must be considered while maintaining financial cost. This research project aims to create a conceptual computer model that simplifies the task of evaluating design options for off-grid photovoltaic system applications using MATLAB environement. A smart and ergonomic optimization algorithm is designed by using Fuzzy-TOPSIS technique which selects the optimal design of an off-grid photovoltaic system. Thus, an ergonomic solar PV Design Optimization software is developed by using MATLAB AppDesigner. The software design displayed the input and output data of the PV system with Fuzzy TOPSIS algorithm. Hence, the off-grid solar PV system designed in MATLAB AppDesigner is viable and readily available for future use